Anti-Popery in early modern England: religion, war and print, c. 1617-1635 - Turnbull, E (2016)
This thesis is about anti-popery in early modern England, how its meanings and political uses in printed literature changed in response to the dramatic developments of the Thirty Years' War. I contend that the languages of anti-popery, though structured by binary oppositions, were being used to express complex, multifaceted views about Catholic states in the 1620s and 1630s. The new perspective that this research offers is two-fold. Firstly, it asserts that anti-popery was an active and flexible tool of English Protestant debate about foreign affairs. 'Popish' tyranny, variously embodied in the Counter-Reformation papacy or Habsburg imperialism, was a malleable concept that adapted its meanings and associations with the political circumstances. Our early modern subjects were capable of separating anti-Catholic beliefs about idolatrous worship from political questions of how to identify, and combat, the threat of papal tyranny. Thus, this thesis argues that a greater range of irenic attitudes towards relations with Catholic powers were circulating than previously thought. Secondly, this thesis argues that several different anti-papal languages were operating alongside, and in competition with, one another in early Stuart political culture. As a fluid set of tropes, associations and prejudices, anti-popery had different meanings for different authors and incorporated a range of political and religious agendas. Anti-popery, therefore, was not simply a tool of Puritan opposition to the non-interventionist policy of the Stuarts, but, I argue, was also compatible with a more moderate or conciliatory attitude to Catholic states, including Habsburg Spain. The printed debates of the 1620s and 1630s expose the tensions that existed between competing ideas about the nature of the external popish threat. By 1635 and the reversal of Protestant fortunes on the Continent, these competing anti-papal ideas were exposing the tensions within England about the nature of its Protestantism, and thus helped precipitate the Civil Wars.